Mechanism of Spin‐Orbit Torques in Platinum Oxide Systems. (15th March 2022) - Nath, Jayshankar; Trifu, Alexandru Vladimir; Gabor, Mihai Sebastian; Hallal, Ali; Auffret, Stephane; Labau, Sebastien; Mahjoub, Aymen; Chan, Edmond; Chaurasiya, Avinash Kumar; Mondal, Amrit Kumar; Yang, Haozhe; Schmoranzerova, Eva; et al.
Abstract: Spin‐Orbit Torque (SOT) Magnetic Random‐Access Memories (MRAM) have shown promising results toward the realization of fast, non‐volatile memory systems. Oxidation of the heavy‐metal (HM) layer of the SOT‐MRAM has been proposed as a method to increase its energy efficiency. But the results are widely divergent due to the difficulty in controlling the HM oxidation because of its low enthalpy of formation. Here, these differences are reconciled by performing a gradual oxidation procedure, which allows correlating the chemical structure to the physical properties of the stack. As an HM layer, Pt is chosen because of the strong SOT and the low enthalpy of formation of its oxides. The evidence of an oxide inversion layer at the ferromagnet (FM)/HM interface is found: the oxygen is drawn into the FM, while the HM remains metallic near the interface. Moreover, the oxygen migrates in the volume of the FM layer rather than being concentrated at the interface. Consequently, it is found that the intrinsic magnitude of the SOT is unchanged compared to the fully metallic structure. The previously reported apparent increase of SOTs is not intrinsic to platinum oxide and instead arises from systemic changes produced by oxidation. Abstract : Heavy metal oxidation has been suggested as a route to high‐efficiency Spin‐Orbit Torque (SOT)—Magnetic Random Access Memories. However, in‐depth characterizations and modeling of a prototypical system, with PtOx as the active layer, indicate a surprising effect: oxygen near the interface is pumped into the ferromagnetic layer. There is no intrinsic increase in SOTs arising from oxidized heavy metals.